Reducing the risk of preterm birth by ambulatory risk factor management - Berger, Richard; Kuon, Ruben-Jeremias (Deutsches Ärzteblatt, 2019)
Background: The preterm birth rate in Germany has remained unchanged at 8–9% since 2009. Preterm birth is the most common cause of neonatal morbidity and mortality. In the absence of a causal treatment, it is important to lower the risk of preterm birth by preventive measures in prenatal outpatient care. Methods: This review is based on pertinent publications from the years 2000–2019 that were retrieved by a selective search in PubMed. Results: The clinical risk factors for preterm birth - known mainly from retrospective cohort studies - include previous preterm birth (adjusted odds ratio [aOR]: 3.6), multiple pregnancy (relative risk [RR]: 7.7), nicotine consumption (aOR: 1.7), and a short uterine cervix, i.e., <25 mm in the second trimester (aOR: 6.9). In women with a short cervix, vaginally administered progesterone significantly lowers the preterm birth rate (22.5% vs. 14.1% for birth before 33 weeks of gestation, RR: 0.62; 95% confidence interval [0.47; 0.81]). Nicotine abstinence is associated with a lower preterm birth rate as well (aOR: 0.91; [0.88; 0,.94]), while working more than 40 hours per week (aOR: 1.25; [1,.01; 1,.54]) and heavy lifting during pregnancy (hazard ratio [HR]: 1.43; [1.13; 1.80]) are associated with a higher preterm birth rate. Avoidance of physical exertion, or bed rest, in the face of impending preterm birth does not lower the preterm birth rate, but it does increase the risk of complications, such as thromboembolism. Conclusion: The meticulous assessment and elimination of treatable risk factors at the outset of ambulatory prenatal care can help lower the preterm birth rate. Further progress can be expected to include the development of causally directed treatments (e.g., changes of relevant environmental and epigenetic factors).
Gesehen am 20.02.2020